The Established Status Epilepticus Trial 2013 - Bleck, Thomas (2013)
Benzodiazepine-refractory status epilepticus (established status epilepticus, ESE) is a relatively common emergency condition with several widely used treatments. There are no controlled, randomized, blinded clinical trials to compare the efficacy and tolerability of currently available treatments for ESE. The ESE treatment trial is designed to determine the most effective and/or the least effective treatment of ESE among patients older than 2 years by comparing three arms: fosphenytoin (fPHT) levetiracetam (LVT), and valproic acid (VPA). This is a multicenter, randomized, double-blind, Bayesian adaptive, phase III comparative effectiveness trial. Up to 795 patients will be randomized initially 1:1:1, and response-adaptive randomization will occur after 300 patients have been recruited. Randomization will be stratified by three age groups, 2–18, 19–65, and 66 and older. The primary outcome measure is cessation of clinical seizure activity and improving mental status, without serious adverse effects or further intervention at 60 min after administration of study drug. Each subject will be followed until discharge or 30 days from enrollment. This trial will include interim analyses for early success and futility. This trial will be considered a success if the probability that a treatment is the most effective is >0.975 or the probability that a treatment is the least effective is >0.975 for any treatment. Proposed total sample size is 795, which provides 90% power to identify the most effective and/or the least effective treatment when one treatment arm has a true response rate of 65% and the true response rate is 50% in the other two arms.